My CPA saved me millions or did he? a case study of professional ethics and the SC2 tax planning strategy - Boneck, Robin; Christensen, David S. (London : Institute of Management Accountants, 2009)
This case study explores the role of the CPA in providing tax planning services to clients using a sophisticated and creative tax planning strategy developed by a fictitious CPA firm for its clients. It provides a framework to teach students ethical standards governing tax practice and rules regulating tax practice before the IRS. It also provides an opportunity for students to contemplate and develop personal standards of practice prior to being confronted with an actual ethical dilemma in practice.
Originally published in Boneck, R. & Christensen, D. S. (2009). My CPA saved me millions or did he? A case study of professional ethics and the SC2 tax planning strategy. IMA Education Case Journal, 2(4), Article 1.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Accountants -- Case studies; Tax accounting -- Case studies